Investigation on Relations of Blood Chemistry Parameters in Bluefish (Pomatomos saltatrix L. 1758) using Multidimensional Scaling Technique - BULUT, MUSA; MENDES, MEHMET; BILEN, SONER; CELIK, IHSAN (Asian Journal of Chemistry, 2010)
The relationships among various blood chemistry parameters of Bluefish (Pomatomus saltatrix L. 1758) were investigated by multidimensional scaling technique (MDS). The results of the MSD technique showed that blood chemistry parameters were affected by seasonal changes, total number of parameters in the model and the interactions between the parameters. The relationships among various parameters were more apparent in winter with a coefficient of 87.8 %, which was followed by fall with 70.5 % and spring with 69.9 %. The results of the statistical analysis also indicated that direct bilirubin, total bilirubin, albumin, uric acid, total protein and low-density lipoproteins parameters of winter Bluefish were associated or similar with each other. The blood proteins did not seem to be related to any of the blood minerals except for K in winter. It was found that the relationships among Cl, K, Na and creatine and between uric acid and cholesterol were high in the fall caught Bluefish. The relationships among the blood parameters of the spring caught Bluefish suggested that high-density lipoproteins, total proteins and cholesterol parameters were associated with each other. It is concluded that MDS may be a valuable tool to study relationships and interactions between various blood chemistry parameters and exogenous factors.